2020
DOI: 10.1055/s-0040-1701217
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Timing of Surgery in Pituitary Apoplexy on Continuously Valued Visual Acuity

Abstract: Background Pituitary apoplexy is often treated urgently, but this is based on studies which assess vision categorically and dichotomizes the time interval between symptom onset and surgery which may introduce bias in measuring an association between the two. Objective This study was aimed to assess for a relationship between continuously valued surgery delay and visual acuity recovery after pituitary apoplexy. Methods In this retrospective study, all patients presenting with symptomatic pit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
(27 reference statements)
1
4
0
Order By: Relevance
“…Those clinical manifestations are generally due to a pituitary or intralesional hemorrhage, more rarely to a rapid growth neoplasm or a severe infectious condition. Although the feasibility and safety of transcranial endoscopic procedures in emergency settings have been recently demonstrated [15], there are no large series yet in the literature about the management of urgencies in trans-sphenoidal endoscopic surgery [16,17], and almost all of them involve PA [18][19][20]. Our series confirms these data, reporting 18 patients (69.2%) affected by PA (13 non-functioning, five secreting prolactin).…”
Section: Discussionsupporting
confidence: 82%
“…Those clinical manifestations are generally due to a pituitary or intralesional hemorrhage, more rarely to a rapid growth neoplasm or a severe infectious condition. Although the feasibility and safety of transcranial endoscopic procedures in emergency settings have been recently demonstrated [15], there are no large series yet in the literature about the management of urgencies in trans-sphenoidal endoscopic surgery [16,17], and almost all of them involve PA [18][19][20]. Our series confirms these data, reporting 18 patients (69.2%) affected by PA (13 non-functioning, five secreting prolactin).…”
Section: Discussionsupporting
confidence: 82%
“…A meta-analysis including 200 patients with PA aimed at evaluating visual recovery comparing early vs. late surgery did not find statistical differences [37]. Likewise, other studies found similar pituitary impairment and significant improvement in outcomes regardless of the timing of surgical intervention [16,17,[38][39][40]. The ongoing multicenter project conducted at Cedars-Sinai Hospital called "Pituitary Apoplexy Surgical Timing and Outcome Registry (PASTOR)" would l provide definitive evidence about treatment approaches and outcomes [41].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, high doses of glucocorticoid are mandatory immediately after PA diagnosis, and neurosurgery is reserved for more severe cases or when the conservative approach fails [11][12][13][14][15]. However, the timing of surgery for improving visual outcomes is a matter of debate [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…A conservative approach using high doses of glucocorticoid is mandatory immediately after diagnosis, and neurosurgery is reserved to more severe cases or when the conservative approach has failed [ 38 , 39 , 40 , 41 , 42 ]. However, there is not agreement on the best timing of surgery when there is visual impairment [ 43 , 44 ].…”
Section: Methodsmentioning
confidence: 99%